Synthesis of soluble polyimides based on ether-linked cyclohexyldiamine and their ultraviolet shielding behavior. (March 2015) - Revathi, Rajamanickam; Prabunathan, Pichaimani; Devaraju, Subramani; Alagar, Muthukaruppan
A series of polyimides (PIs) based on ether-linked cyclohexyldiamine were prepared using pyromellitic dianhydride (PI-1), benzophenone dianhydride (PI-2), naphthalene dianhydride (PI-3), and perylene dianhydride (PI-4) in 1-methyl-2-pyrrolidone (NMP) medium to obtain respective polyamic acids and are subsequently converted into PIs through thermal imidization. The resulting PIs were characterized by Fourier transform infrared, X-ray diffraction, thermogravimetric analysis, differential scanning calorimetry, and impedance analyses. In addition, the ultraviolet (UV) shielding ability of PIs was also studied and discussed. The vibrational analysis confirms the imidization, and the XRD profile indicates the amorphous nature of the resulting PIs. The PIs synthesized in the present work exhibit good solubility in organic solvents such as NMP, dimethylformamide (DMF), and dimethyl sulfoxide (DMSO). The PI-4-based imide possesses very good solubility with the highest glass transition temperature value of 256°C, highest char yield of 50.16%, highest dielectric constant of 3.9 and higher UV shielding performance of 89% than those of other PIs. Further, the good solubility also makes them useful for coating applications in aerospace and liquid crystal displays.